EFEKTIVITAS PHYPHOX SEBAGAI MEDIA PEMBELAJARAN PADA EKSPERIMEN GERAK JATUH BEBAS - Cintya Josefin Kauwo; Treesje Katrina Londa; Alfrits Komansilan (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2022)
Since the Covid-19 pandemic has resulted in practicum activities not running optimally. To overcome these obstacles, the virtual laboratory using the Phyphox application can be used as a distance learning medium. This study aims to determine the effectiveness of the Phyphox application in the Free Fall Motion experiment as a learning medium. This research is pre-experimental research with one group pretest-posttest research design. The research subjects are students of the VIII semester of the Physics Department, Manado State University 2020/2021. Collecting data using tests with test instruments in the form of essays and science process skills and affective assessment using rubrics. The average pretest result increased to 42.67 to 86.67 on the average posttest result. The average results of the assessment of science process skills and affective assessment are in good criteria (66-79%) and very good criteria (80-100%). Obtaining N-Gain scores from each student, there were 11 students in the high N-Gain category with a percentage of 73% and as many as 4 students in the medium N-Gain category with a percentage of 27%. The result of the average percentage of N-Gain from 15 students is 76.4%. The results of this study indicate that the use of the Phyphox Application is effectively used in free fall motion experiments as a learning medium.